SYMPTOMS AND CAUSES OF TRAUMATIC EXPERIENCES IN LEILA S. CHUDORI’S NOVEL FOR NADIRA - Elsa Ardani; Susi Ekalestari (Universitas Islam Sumatera Utara, 2023)
This study aims to analyze the traumatic experiences and their effects in the novel For Nadira, written by Leila S. Chudori. She is an Indonesian author who has written various journal and literary works, one of which was awarded the Khatulistiwa Literary Award in 2013. A traumatic condition occurs due to events (single or continuous) whose intensity is beyond everyday human experience or which are interpreted as extraordinary by individuals, causing feelings of anxiety, fear, and helplessness that have a negative impact on the quality of life physically, mentally, spiritually, and socially. The writers chooses this title to determine two objectives: first, to reveal the symptoms of the traumatic experiences, and second, to explain the causes of the traumatic experiences using the theory of trauma from Irwanto and Hani Kumala. This research is completed using the descriptive-qualitative method. The data are taken from the novel For Nadira, Leila S. Chudori. The effects of traumatic experiences can make a person feel panic, constant fear, sensitive, angry and have a sense of hatred towards the people involved in the trauma experience.